Pengaruh Kesadaran Wajib Pajak, Pengetahuan Pajak, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Roda Dua Di Daerah Terluar, Tertinggal, Terdepan (3T) (Studi Kasus Kecamatan Sikakap Kab. Kepualaun Mentawai) - Dzaki Akbar Ramadhan Khamel; Ingra Sovita (CV. ITTC INDONESIA, 2024)
The purpose of this study was to analyze Taxpayer Awareness, Tax Knowledge and Tax Sanctions on Taxpayer Compliance of two-wheeled motorized vehicles in disadvantaged, outermost, foremost (3t) areas (Case Study of Sikakap District, Kepulauan Mentawai). Based on the research results, the following four things were concluded. First, Taxpayer Awareness has a positive and significant effect on taxpayer compliance for two-wheeled motorized vehicles in the outermost, leading and disadvantaged areas (3T) with a significant value of 0.009 < 0.05. Second, Tax Knowledge has a positive and significant effect on Taxpayer compliance with two-wheeled motorized vehicles with a significant value of 0.021 < 0.05. Third, Tax Sanctions have a positive and significant effect on Taxpayer compliance for two-wheeled motorized vehicles with a significant value of 0.01 < 0.05. Fourth, research results using the F test showed that simultaneously Taxpayer Awareness, Taxpayer Compliance, Tax Sanctions had a positive effect on Taxpayer compliance with two-wheeled motorized vehicles with a significant value of 0.000 and a calculated F value of 418,483 > F table 17,750